2012
DOI: 10.1177/0961203312436853
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow abnormalities in neurologically asymptomatic patients with primary antiphospholipid syndrome

Abstract: Asymptomatic patients with PAPS can have significantly increased MFVs. These alterations may be the consequence of accelerated atherosclerosis, PAPS vasculopathy or both. Whatever the cause, these findings can represent a risk for stroke in PAPS patients that needs the trial of other therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…8 The PI is an important haemodynamic parameter that linearly correlates with cerebral microvascular tone, blood flow resistance and impedance. 8 Other studies have evaluated PI in patients with SLE 40,49 and APS 6 and found no differences when compared with healthy volunteers. 6 In our series, patients with APS (either PAPS or SAPS) had a trend to present more intracranial stenosis than healthy volunteers.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…8 The PI is an important haemodynamic parameter that linearly correlates with cerebral microvascular tone, blood flow resistance and impedance. 8 Other studies have evaluated PI in patients with SLE 40,49 and APS 6 and found no differences when compared with healthy volunteers. 6 In our series, patients with APS (either PAPS or SAPS) had a trend to present more intracranial stenosis than healthy volunteers.…”
Section: Discussionmentioning
confidence: 98%
“…8 Other studies have evaluated PI in patients with SLE 40,49 and APS 6 and found no differences when compared with healthy volunteers. 6 In our series, patients with APS (either PAPS or SAPS) had a trend to present more intracranial stenosis than healthy volunteers. Intracranial stenosis in patients with APS could be due to an aPLinduced vasculopathy or even intracranial atherosclerosis.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations